Efecto de Niveles de Fertilización en “Drench" en la productividad de Dos Variedades de Ají pimentón (Capsicum annum L), en la zona de Lamas - Rámirez Flores, Juan Manuel (2007)
This research was carried out in "El Pacifico" farm, Killoalpa sector, in Lamas district and province, San Martin's region , located in 06° 20• 15•• south latitude, 76° 30• 45 west longitude and 814 meters above sea level, on a soil of franc sandy texture with low disponibility of elements (N,P.K,Ca Mg). The aims were: 1) Determine optimum doses of N P, K through the drench fertilization method in chili pepper culture. 2) Evaluate the effect of the drench fertilization levels in the productivity of chili pepper varieties. 3) Make the economic analysis of the studied treatments. The statistical model was a randomized complete block design, with a 5 X 2 factorial arrangement , with 3 repetitions and 1O treatments, using 30 experimental units, 4 fertilization doses were studied , compared to the standard sample that it hadn't any fertilization , being a total of 5 treatments , in two varieties of chilli pepper (ANASAC , ltalian sweet) : T1 and T2 (150-100-90) , T3 and T4 (130-90-90) , T5 and T6 (200-100-100) , T7 and T8 (250-90-80) . T9 and T10 (0-0-0), besides were added other micronutrients (B,Zn,Fe,Cu,Mo,Co) , the distance was 0.80 m between rows and 0.80 m between plants. The results showed that the treatments T5 and T6 (200-100-100) were the best having yields of 17 700 and 20 590 kg/ ha per variety, with net utilities of S/. 18555.74 and S/. 20 890.74 nuevos soles.